2011
DOI: 10.1089/vbz.2011.0639
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Influenza A Antibodies in Yellow-Legged Gull (Larus michahellis) Eggs and Adults in Southern Tunisia

Abstract: Investigating the prevalence of anti-influenza A viruses (AIV) antibodies in wild birds can provide important information for the understanding of bird exposure to AIV, as well as for prevention purposes. We investigated AIV exposure in nature by measuring the prevalence of anti-AIV antibodies in the nests and adults of an abundant and anthropophilic waterbird species common around the Mediterranean sea, the yellow-legged gull (Larus michahellis). Sampling took place in two colonies located in the gulf of Gabè… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…In birds, adult females that have been exposed to infectious agents can develop humoral immune responses and transfer some of the antibodies produced to the yolk of their eggs [50], [51]. There is a positive correlation between the amount of antibodies in the egg yolk and the amount of antibodies in the plasma of breeding females at the time of laying [52], [53]; therefore, egg yolk antibodies can reflect a female's prior exposure to infectious agents. This indirect method can be useful if the host immune response is detectable for a relatively long time period [53], [54], which has been shown to be the case for WNV in other avian species [55], [56].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In birds, adult females that have been exposed to infectious agents can develop humoral immune responses and transfer some of the antibodies produced to the yolk of their eggs [50], [51]. There is a positive correlation between the amount of antibodies in the egg yolk and the amount of antibodies in the plasma of breeding females at the time of laying [52], [53]; therefore, egg yolk antibodies can reflect a female's prior exposure to infectious agents. This indirect method can be useful if the host immune response is detectable for a relatively long time period [53], [54], which has been shown to be the case for WNV in other avian species [55], [56].…”
Section: Introductionmentioning
confidence: 99%
“…There is a positive correlation between the amount of antibodies in the egg yolk and the amount of antibodies in the plasma of breeding females at the time of laying [52], [53]; therefore, egg yolk antibodies can reflect a female's prior exposure to infectious agents. This indirect method can be useful if the host immune response is detectable for a relatively long time period [53], [54], which has been shown to be the case for WNV in other avian species [55], [56]. Partial clutches can be sampled over a large area that encompasses several host populations, and there is no need to capture breeding adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating antibodies to H13 AIV in adult ring-billed gulls ( Larus delawarensis ) ranged between 82 and 92%, with antibody prevalence in 3-wk-old chicks ranging between 5 and 30% [10]. In yellow-legged gulls ( Larus michahellis ), 81% of females had circulating AIV antibodies and 51% of their eggs received these antibodies maternally [11]. In this species it was shown that maternal AIV antibodies in eggs reflected the circulating AIV antibodies of the laying females, and that the first-laid eggs received highest levels of maternal antibodies [12].…”
Section: Introductionmentioning
confidence: 99%